Determining of the Prospective Teachers’ Understadings of Electrochemistry - Bayrakçeken, Samih; Yilmaz, Adem (Elsevier BV, 2015)
AbstractThe aim of this study was to determine of prospective teachers’understandings related to electrochemistry. Qualitative and quantitative research techniques were used together in the study. A concept test consisted of 20 items for electrochemistry; interviews and focus group discussion were used as data collecting tools. Data were collected after the subject of electrochemistry was taught in the scope of general chemistry lesson. Sample of the study consisted of 95 prospective teachers studying in the first grade of elementary science teaching department in an education faculty in 2011-2012 semester. The electrochemistry concept test was given to the sample at the end of electrochemistry unit. The interviews and the focus group discussion were made with the prospective teachers chosen according to the results of concept test. Findings of the study showed that the prospective teachers’ understandings of electrochemistry were inadequate and there were many misconceptions. Many misconceptions were found different from previously detected misconceptions in literature.
Keywords: Electrochemistry; Misconception; Interview; Concept Test; Focus Group Discussion.; 13. Climate action; 4. Education